Análisis del gasto ejecutado anual en salud pública proveniente del sistema general de participaciones en municipios colombianos de 2016 a 2019 (2021)
In Colombia, the knowledge we have about the public health spending and the factors that may influence this behavior, is limited. Several studies have described how variables such as women in politics or poverty, are factors that can influence the way this resources are used. This study analized the behavior of the public health resources from the Sistema General de Participaciones and that was used by all de municipalities of Colombia during the period from 2016 to 2019. The results showed that multidimensional poverty was associated with the public health spending for the municipalities of groups 4, 5 and 6. In the other hand, there was no association between the presence of women in different governmet positions and ethnic/racial population with the public health spending. It is important to strengten and create mandatory criteria for public health spending in the municipalities, taking into acount that aproximately 93% of these showed an association with multidimensional poverty.